Clinical profile of kidney involvement preceding diagnosis of multiple myeloma; a single center experience - Manish R Balwani; Manoj R. Gumber; Pankaj R. Shah; Vivek B. Kute; Himanshu V. Patel; Divyesh P. Engineer; Dinesh N Gera; Umesh Godhani; Rajesh Singh Gautam; Hargovind L. Trivedi (Society of Diabetic Nephropathy Prevention, 2016)
Introduction: The kidneys are involved in significant number of patients with multiple myeloma (MM) who can present with acute or chronic renal failure, nephritic syndrome, non-nephrotic proteinuria or tubular function defects. Objectives: To assess the clinical profile of kidney involvement preceding diagnosis of multiple myeloma Patients and Methods: Renal involvement in 29 cases with MM admitted over an 18-month period to our tertiary care center was retrospectively examined. Diagnosis of MM was confirmed by two or more of the following four features: lytic bone lesions, serum or urine monoclonal peak, Bence-Jones proteinuria, and greater than 20% plasma cells in bone marrow. Results: Renal disease was present in all patients before MM was diagnosed. Non-steroidal anti-inflammatory drugs (NSAIDs) was the most common precipitating factor for acute kidney injury (AKI). All 29 patients received combination chemotherapy of bortezomib, dexamethasone and thalidomide. More than half of the total number of patients did not complete chemotherapy because of death or lost to follow-up. Twenty-two of 29 patients required hemodialysis support. AKI was the most common renal presentation of MM. Four patients with AKI had complete renal recovery. Eleven patients who required hemodialysis support initially later on recovered to non-dialyzable range of renal failure. Seven patients became hemodialysis dependent. Twelve patients died from infection, uremia or hyperkalemia. Nine patients lost to follow up. Remission of MM was seen in 8 patients who completed chemotherapy. Conclusion: In our study AKI is the most common renal presentation preceding the diagnosis of MM. Reversal of renal function was achieved with chemotherapy and high flux hemodialysis in few cases.